Analisis Peran Pemerintah dalam Mendorong Moderasi Islam di Sumatra Utara - Adi Muflih Adi; Alfi Rahmat; Alya Qais Tsaabitah; Muhammad Faiz Muhtadi Siregar; Wiki Helmi Andrean (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study discusses the role of the government in promoting Islamic moderation in North Sumatra. Through qualitative and quantitative data analysis from 15 academic sources, the author concludes that the government’s main strategy is to make education an effective tool to preserve moderate values. Interfaith dialogue forums are an important platform for local residents to understand and appreciate differences. The results of the study indicate that government efforts have succeeded in reducing indicators of radicalism and increasing the level of social tolerance among the community. However, there are still several active obstacles such as economic instability and ignoring the participation of non-Muslim communities that must be further addressed by the government so that the implementation of Islamic moderation remains stable and develops positively. Integration of moderate values ​​in the context of local culture is a strategic step towards a harmonious and prosperous society.